Her father's daughter : gender, power, and religion in the early Spanish kingdoms - Pick, Lucy K., 1966- (Ithaca : Cornell University Press, 2017)
"Considers a group of royal women in the early medieval kingdoms of the Asturias and of León-Castilla; their lives say a great deal about structures of power and the roles of gender and religion within the early Iberian kingdoms. Pick examines these women, all daughters of kings, as members of networks of power that work variously in parallel, in concert, and in resistance to some forms of male power, and contends that only by mapping these networks do we gain a full understanding of the nature of monarchical power"--
Visigothic inheritance, Asturian monarchy -- Virgins and martyrs -- Networks of property, networks of power -- Memory, gift, and death.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on November 27, 2018).
JSTOR
Keywords: Upper class women -- Spain -- History -- To 1500.; Women and religion -- Spain -- History -- To 1500.; Monarchy -- Spain -- History -- To 1500.; Sex role -- Spain -- History -- To 1500.; Power (Social sciences) -- Spain -- History -- To 1500.; Women -- Spain -- History -- Middle Ages, 500-1500.; Spain -- History -- 711-1516.; Femmes -- Espagne -- Histoire -- 500-1500 (Moyen Âge); SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; HISTORY -- Medieval; Monarchy; Power (Social sciences); Sex role; Upper class women; Women and religion; Women -- Middle Ages; Spain; To 1516; History